Study on Non-knotted Barbed Suture with Silk Fibroin Structure (Journal of Fiber Bioengineering and Informatics, 2022)
Surgical sutures allow for wound closure and tissue closure. Ordinary sutures require complicated knotting and manipulation. A kind of barbed silk thread was developed in this paper. The structure of barbed suture was tested and analyzed by infrared absorption spectroscopy and X-ray diffraction. The results showed that ethanol immersion and high pressure treatment changed the crystal structure of silk fibroin barb and increased the crystallinity of silk fibroin protein. The solubility and mechanical properties of silk fiber barbs showed that the solubility rate of silk fiber barbs was low, but the mechanical properties were strong. It was found that the barbs of silk fibroin were closely bound to the silk thread and formed a regular barb structure on the silk thread. In this paper, different barb Angle sutures of 30°, 45° and 60° were prepared. And the mechanical properties test results showed that the 45° barb sutures have a better stitching effect. This barbed sutures are expected to be used for tissue suturing.